PENGARUH PENDEKATAN PROJECT BASED LEARNING TERHADAP KEMANDIRIAN ANAK - ratna nila puspitasari (Jurnal CARE (Children Advisory Research and Education), 2020)
Independence is an attitude or behavior that is not easy to depend on others in completing their tasks. Independence in early childhood begins with the ability to make choices, dare to decide on their own choices, responsible for accepting the consequences that accompany their choices, self-confidence, directing themselves, developing themselves, adjusting to their environment and dare to take risks on their choices. Low independence in early childhood is an obstacle for children to move to the next level. The purpose of this study is to determine the effect of the project based learning approach to the independence of children aged 4-5 years at Dharma Wanita Dadapan Balong Kindergarten. This research uses a quantitative approach using an experimental method with a pre-experimental research design. Post-test one-group design. The subjects of this study were 12 children in group A at Dharma Wanita Dadapan Balong Kindergarten. Data collection techniques through participant observation and documentation in the form of photographs of activities and plans for implementing daily learning. Data processing using t-test data analysis. The results of data analysis obtained a value of -6.76 and a value of 2.074 then (2.074> -6.76) and Ha accepted. Based on the analysis of these data, there is a significant influence between the project based learning approach on children's independence